Environmental friendly polymer based recycled Nitrile Gloves Incorporated with poly(lactic acid)/graphene nanoplatelets binary blends - Bijarimi, Mohd; Jaro, Vera Saban; Mulkiyan, La Ode Muhammad Zuhdi; Mat Desa, Mohd Shaiful Zaidi; Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi (Wiley Periodicals, LLC., 2025)
The waste issue from the widespread use of nitrile gloves emphasize the environmental and health risks associated with improper disposal. This study introduces an innovative approach by incorporating recycled nitrile gloves made from acrylonitrile butadiene (rNBR) into a composite with poly(lactic acid) (PLA) and graphene nanoplatelets (GNPs) (1, 2, and 3 phr). The results showed a maximum improvement in mechanical properties at a PLA/rNBR blend ratio of 60:40 wt%, demonstrating a balance between stiffness and toughness compared to other binary blend ratios. The incorporation of GNP enhanced the values of Young's modulus, tensile strength, and elongation, respectively. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) recorded that the thermal stability of PLA/rNBR tends to increase with the loaded GNP. The morphological properties observed through scanning electron microscopy (SEM) revealed that the PLA/rNBR surface exhibited a nonhomogeneous distribution, leading to the formation of numerous voids and low adhesion. However, the good distribution of GNP within the matrix contributed to greater homogeneity, thereby reducing defects caused by rubber crumbs and voids in the PLA/rNBR fracture. Based on this research, this strategy offers a promising solution to address the environmental challenges posed by personal protective equipment waste